Human monoclonal antibodies: the residual challenge of antibody immunogenicity. - Waldmann, H (2014)
One of the major reasons for seeking human monoclonal antibodies has been to eliminate immunogenicity seen with rodent antibodies. Thus far, there has yet been no approach which absolutely abolishes that risk for cell-binding antibodies. In this short article, I draw attention to classical work which shows that monomeric immunoglobulins are intrinsically tolerogenic if they can be prevented from creating aggregates or immune complexes. Based on these classical studies two approaches for active tolerization to therapeutic antibodies are described.